USE OF FERTILIZERS AND BIO MEDICINE FOR SUNFLOWER ON ORDINARY CHERNOZEM (BLACK SOIL) - E. V. Agafonov; G. E. Mazhuga; A. V. Vatschenko (Зерновое хозяйство России)
In 2012-2013 we carried out field trials of sunflower hybrid ‘Patriot’ fertilizing it with bio fertilizers on ordinary chernozem of the central part of the Rostov region. Such fertilizers as ammonium phosphate and ammonium nitrate were added during presowing cultivation and bio fertilizer with microorganisms PG-5, 30 P, 7, 17-1 were used for seed processing. The use of N40Р50 dose of fertilizer increased sunflower productivity, oil content and oil yield per hectare on 24,6%, 3,2% and 33,7% respectively in comparison with a standard. The increase of the dose of phosphorus up to 100 kg/ha with presence of 15 mg/kg of moving phosphorus in soil didn’t greatly change these indexes. Nitrogen increase up to 80 kg/ha reduced these indexes but only with a high content of nitrogen in soil.  The seed treatment with bio medicine with microorganisms 7 and PG-5 gave good results. The productivity increased on 20,5%, the oil yield on 27,6 and 24,1%. The variants 30P and 17-1 are unstable to moisture deficit in soil and boiling temperature, which occurred in both years of trials.